Odpowiedź :
1)
[tex] - 5(2x - 7) = 4 - 3(x + 5)[/tex]
[tex] - 10x + 35 = 4 - 3x - 15[/tex]
[tex] - 10x + 3x = - 11 - 35[/tex]
[tex] - 7x = - 46[/tex]
[tex]x = \frac{46}{7} = 6 \frac{4}{7} [/tex]
2)
[tex] \frac{x - 3}{4} + 1 = \frac{1}{4} - 3x[/tex]
[tex]x - 3 + 4 = 1 - 12x[/tex]
[tex]x + 12x = 1 + 3 - 4[/tex]
[tex]13x = 0[/tex]
[tex]x = \frac{0}{13 } = 0[/tex]
3)
[tex]3x - 2 = 6 - x[/tex]
[tex]3x + x = 6 + 2[/tex]
[tex]4x = 8[/tex]
[tex]x = 2[/tex]
4)
[tex]3 - (x - 3) = x - 3[/tex]
[tex]3 - x + 3 = x - 3[/tex]
[tex] - x - x = - 3 - 3 - 3[/tex]
[tex] - 2x = - 9[/tex]
[tex]x = \frac{9}{2} = 4 \frac{1}{2} [/tex]
5)
[tex](x + 2)(3x - 1) = (3x - 1)(x - 2)[/tex]
[tex]3 {x}^{2} - x + 6x - 2 = 3 {x}^{2} - 6x - x + 2[/tex]
[tex]6x + 6x = 2 + 2[/tex]
[tex]12x = 4[/tex]
[tex]x = \frac{4}{12} = \frac{1}{3} [/tex]